Delayed spinal cord infarction following anterior cervical surgical decompression - Khan, Muhammad Faheem (BMJ Case Rep, 2017)
Anterior cervical discectomy and fusion (ACDF) for cord compression is a safe and effective procedure with good outcomes. However, worsening of myelopathy is the most feared adverse event of the surgery. We report the case of a 36-year-old male patient who presented with an acute non-traumatic C5–6 cervical disc herniation causing incomplete quadriparesis. He underwent an uncomplicated ACDF at C5–6, and after an initial period of improvement, he developed a delayed onset of an anterior cord syndrome on day 3, without any discerning cause. We have reviewed similar cases reported in the literature and believe that our patient’s postsurgical course is consistent with a delayed ischaemic/reperfusion injury to the cord following surgical decompression and restoration of blood flow through the anterior spinal artery and we make suggestions for management of such clinical events.